Andropaniosides A and B, two new ent-labdane diterpenoid glucosides from Andrographis paniculata. (February 2020) - My, Nguyen Thi Thuy; Hanh, Tran Thi Hong; Cham, Pham Thi; Cuong, Nguyen Xuan; Huong, Tran Thu; Quang, Tran Hong; Nam, Nguyen Hoai; Minh, Chau Van
Graphical abstract: Highlights: 7 compounds were isolated from Andrographis paniculata by chromatographic methods. 2 new and 5 known compounds were identified by analysis of NMR and MS spectra. Cytotoxicity properties toward LNCaP, HepG2, KB, MCF7, and SK-Mel2 cancer cells. NO inhibitory effects in LPS-stimulated RAW264.7 cells. Abstract: Two new ent -labdane diterpenoid glucosides, andropaniosides A and B, along with five known analogs, andrographiside, neoandrographolide, andropanoside, 14-deoxy-11, 12-didehydroandrographiside, and 19- O - β -D-glucopyranosyl- ent -labda-8(17), 13-dien-15, 16, 19-triol were isolated from a methanol extract of the aerial parts of Andrographis paniculata . Their chemical structures were identified by the comprehensive spectroscopic methods, including 1D and 2D NMR and mass spectra. In addition, their cytotoxic effects toward LNCaP, HepG2, KB, MCF7, and SK-Mel2 human carcinoma cells and NO inhibitory effects in LPS-stimulated RAW264.7 cells were also evaluated.